Catalyst-Free Reduction of Aldimines with Hantzsch Esters - Li, Jianhui; Wang, Zhouyu; Jiang, Zhenju; Jiang, Shengqian; Xiong, Lilin (Asian Journal of Chemistry, 2011)
An efficient catalyst-free reduction of aldimines is reported. In the absence of any additional catalysts, a series of N-aromatic aldimines were reduced with Hantzsch esters as the hydrogenation source. Moderate to excellent isolated yields (up to 99 %) were obtained under mild conditions.